The Prominent Of Local Products Following Boycott Calls - Leni Susanti; Najmudin Najmudin; Sudarto Sudarto (International Journal of Business and Quality Research, 2024)
Boycotting is a potent strategy for generating awareness, particularly on current matters. It plays a role in driving societal change and actively involves individuals in addressing the pressing issues of the globe. This study aimed to investigate the influence of customer’s perspective and economics independence to purchase intention in order to escalate the sales of domestic products. To meet our goals, we utilized both secondary and primary data sources. First, we reviewed the literature concerning customer’s perception of boycotting, economics independence in order to elevate the purchase intention of customer on local products. Second, to gather the primary data, this study utilizes descriptive-correlational quantitative research methods and employing Smart-PLS for model evaluation. A random sample of 18–55-year-olds of diploma, undergraduate, master and doctoral students. The results show that customer’s perception may elevate the local product’s sales due to the awareness for not buying the products that support Israel. Economics independence also influence the prominence of local product’s selling. It may happen since local producers can provide the same product that many people boycotted. Economics independence triggered positive perception of customer to buy local products. The independence to not import products affiliated with Israel is believed to be able to increase the prestige of local products. This is because people already understand what they are doing, the risks they will face and know what to buy.